Pharmacokinetics and safety of deltoid or gluteal injection of aripiprazole lauroxil NanoCrystal® Dispersion used for initiation of the long-acting antipsychotic aripiprazole lauroxil. (July 2019) - Hard, Marjie L.; Wehr, Angela; von Moltke, Lisa; Du, Yangchun; Farwick, Sarah; Walling, David P.; Sonnenberg, John
Background: Aripiprazole lauroxil (AL), a long-acting injectable antipsychotic for the treatment of schizophrenia in adults, can be started with either 21 days of daily oral aripiprazole supplementation or a 1-day initiation regimen consisting of a single injection of a NanoCrystal ® Dispersion formulation of AL (ALNCD ) and a single dose of 30 mg oral aripiprazole. This phase I study assessed the pharmacokinetics and safety of deltoid versus gluteal ALNCD injections. Methods: Patients with schizophrenia or schizoaffective disorder ( N = 47) were randomized 1:1 to receive a single intramuscular dose of ALNCD in the deltoid or gluteal muscle. Plasma samples were collected over 85 days to measure ALNCD concentration by injection site. Relative aripiprazole bioavailability for deltoid versus gluteal injection was assessed based on area under the curve (AUC∞ and AUClast ) and maximum concentration (Cmax ) values. Adverse events were monitored throughout the study. Results: Plasma aripiprazole concentrations after a single ALNCD injection were comparable between deltoid and gluteal administration. Mean maximum plasma aripiprazole concentrations were 196.1 ng/ml (deltoid) and 175.0 ng/ml (gluteal). Exposure to aripiprazole was similar, with mean AUC∞ values of 6591 day × ng/ml for deltoid and 6437 day × ng/ml for gluteal. Aripiprazole bioavailability was not significantly different between injection sites. ALNCD administration in the deltoid or gluteal muscle was well tolerated, with similar safety profiles at both sites. Conclusion: ALNCD demonstrated similar exposure and safety profiles between the two administration sites, suggesting that ALNCD can be given in either the gluteal or the deltoid muscles as a component of the 1-day initiation regimen for AL.